Law Enforcement of The Criminal Act of Distribution of Cigarette Without Excise (Empirical Review of The Enforcement of Law Number 39 Of 2007 at Kediri Customs) - Sanggarningrum, Meylina; Sunaryo, Sidik; Haris (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Abstract  Received: 2024-10-12 Revised: 2024- 10-23 Accepted: 2024-12-11   Keywords: Law enforcement, Duty Free Cigarettes, Law Number 39 of 2007 Weak law enforcement regarding the circulation of cigarettes without excise stamps in the Kediri Customs and Excise area, causing huge losses to the state. The aim of this research is to determine law enforcement regarding the distribution of cigarettes without excise stamps in the City of Kediri based on Law Number 39 of 2007 and the ideal solution in overcoming the problem of law enforcement regarding the distribution of cigarettes without excise stamps in the City of Kediri. This research is empirical legal research. This research uses primary data, namely the results of interviews with Kediri City Customs and Excise regarding law enforcement for the criminal act of distributing cigarettes without excise stamps as well as secondary data using the provisions of Law no. 39 of 2007 and other regulations relating to excise crimes, legal books, legal theory, and previous research that is considered relevant. The research uses descriptive analytical techniques. The results of this research show that the number of perpetrators who commit criminal acts is not comparable to the number of law enforcement officers who are in the field enforcing cigarette excise tax distribution. The relatively minimal facilities for arresting individuals involved in distributing cigarettes without excise stamps, as well as the lack of knowledge of the public who do not understand the existence of cigarettes without excise stamps, are problems in implementing law enforcement against the distribution of illegal cigarettes. Efforts to overcome the problem of law enforcement regarding the criminal act of distributing cigarettes without excise stamps in Kediri City can be done by collaborating with other law enforcement agencies, carrying out stricter supervision, and adding units or work units to APH on a smaller scale to be distributed in areas of authority. Kediri City Customs office